Diaspora as an ethno-cultural digital communication subject of foreign students in Russia - K. D. Kunilova; T. N. Kameneva; M. V. Vorobyev (Цифровая социология)
The article is devoted to the diaspora study as an ethnocultural communication subject of foreign students in the university educational environment, including the development conditions of interaction digital forms (social networks, messengers, the Internet). The main study purpose is to identify the key functions of the ethnic community, the specifics of the diaspora not only as a socio-cultural phenomenon, but also as an active and influential subject which can play a decisive role in communication processes. The authors turn to the analysis of the accumulated theoretical material, cite as an example the results of a sociological study conducted with a questionnaire survey. The results of the sociological study showed that for foreign students who study at universities in a provincial city (Kursk) and a million-plus city (St. Petersburg), the diaspora, as well as the opportunity to be part of it, plays a fundamental role. For students who have come to study in a small town, the diaspora is significant. There they can find help and support, new forms of leisure, obtain enough information about rules and regulations of the new community. Students who arrive to study in a big city experience cultural shock, may be lost and need special support due to a long period of adaptation. The novelty of the sociological research lies in the fact that a comparative analysis of the diasporic significance for foreign students studying in Kursk and in St. Petersburg is given. The obtained data are used to analyse the current situation in the educational environment. In the future it is planned to conduct periodic wave studies to identify changes in the student environment.